Globalisation and the Colonising State of Mind - Jackson, Moana (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: colonisation; globalisation; neoliberalism; protest

Māori and the United Nations - Charters, Claire (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: UNDRIP; globalisation; neoliberalism; protest; united nations

A Small Issue of Sovereignty - Bargh, Maria (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: history; neoliberalism; political Ideologies; protest; sovereignty; tino rangatiratanga; trans-pacific partnership

We Are Everywhere - Bargh, Maria; Tuiono, Teanau (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: activism; neoliberalism; protest; tino rangatiratanga

Blunting the System: The Personal is Political - Sykes, Annette (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: activism; law; neoliberalism; waitangi tribunal

Māori Development and Neoliberalism - Bargh, Maria (Resistance: an Indigenous response to neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: development; history; neoliberalism; political Ideologies; protest

From new paternalism to new imaginings of possibilities in Australia, Canada and Aotearoa/New Zealand: Indigenous rights and recognition and the state in the neoliberal age - Bargh, Maria; Howard-Wagner, Deirdre; Altamirano-Jimenez, Isabel (The Neoliberal State, Recognition and Indigenous Rights, 2018)
The election of Evo Morales as the first indigenous President of Bolivia in 2005 is widely credited to the Cochamba Water War (Spronk 2007: 8). The Cochamba Water War progressed from an indigenous movement and a specific issue to the creation of an indigenous political party and election of the first indigenous President. The Bolivian water war, the Puebla Panama Plan in Mexico, the Mackenzie Valley pipeline in Canada (Altamirano‐Jiménez 2004) and Māori resistance to the neoliberal agenda from 1984 onwards (Bargh 2007: 26) inspired much theorising about indigenous people successfully contesting neoliberalism (AltamiranoJiménez 2004, Bargh 2007, Spronk 2007: 8, Postero 2007). Bargh and others, for example, documented not only ‘overt Māori resistance to neoliberal policies, but also more subtle stories of activities, which The neoliberal state, recognition and indigenous rights implicitly challenge neoliberal practices and assumptions by their support for other ways of living’ (Bargh 2007: 1). Scholars make visible the persistence of the colonial in the concrete and material conditions of everyday neoliberal governance and life (Howard-Wagner & Kelly 2011: 103). As Bargh (2007), Altamirano-Jiménez (2013), Howard-Wagner (2010b, 2015) and others note, indigenous categorisations of neoliberal practices as a form of colonisation relate to a concern that neoliberalism in its multiple forms poses a threat to indigenous ways of life. This scholarship also critically reflects on the reshaping of the relationship between the state and indigenous peoples under neoliberalism (Altamirano-Jiménez 2004, Bargh 2007, Howard-Wagner 2009). For example, it draws attention to the increasing intervention in the lives of indigenous peoples (Howard-Wagner 2007, 2009, 2010a, 2010b) and the dispossession of indigenous people through privatisation (Wolfe 2006, Howard-Wagner 2012, Altamirano-Jiménez 2013, Coulthard 2014). It does not, however, preclude agency, resistance and decolonisation. Interpretive micro-studies about indigenous peoples’ engagement with neoliberalism provide particular value. They tell us about actually existing neoliberalism in the context of intervention in the everyday lives of indigenous peoples, contests over rights, contests over policy and the complex decisions indigenous people are making about how to protect their rights and navigate diverse economies involving neoliberal policies and practices.
Keywords: crown policy; neoliberalism; treaty obligations; waitangi tribunal; water management; water rights